Systematic Review of Socio-Emotional Values Within Organizations - Pascucci, Tancredi; Cardella, Giuseppina Maria; Hernández-Sánchez, Brizeida; Sánchez-García, Jose C. (Frontiers in Psychology, 2022)
Theory of Separation assumes, with a provocation, that an organization can’t conciliate profits and social function and different authors try to product papers to contrast it. Organization can conciliate these two missions, apparently contrasting, considering emotions, especially moral emotions to create a genuine motivation to focus on goals beyond the simple economic earning and protecting organization or groups of people from dysfunctional attitudes and behaviours. Emotional and social values are an important topic to be enforced for the research about stakeholders accountability, which grant an ethic decision process by organizations. In this research review on SCOPUS we reveal an increasing trend about records on this topic, where there 2019 has been more prolific than 2020 and most 5 involved countries are USA, UK, Australia, Canada, India. Using VosViewer we have separated this record in 6 different clusters regarding: organization performance, organization wellbeing, interpersonal relation, hospital patient management, working teams, employer development.